222k views
3 votes
6(3-x) = -4 (2x-1) please i need help

User Cyral
by
5.5k points

2 Answers

4 votes

Answer: x = -7

Explanation:

Let's solve your equation step-by-step.


6(3-x)=-4(2x-1)

Step 1: Simplify both sides of the equation.


6(3-x)=-4(2x-1)\\(6)(3)+(6)(-x)=(-4)(2x)+(-4)(-1)\\18+-6x=-8x+4\\-6x+18=-8x+4

Step 2: Add 8x to both sides.


-6x+18+8x=-8x+4+8x\\2x+18=4

Step 3: Subtract 18 from both sides.


2x+18-18=4-18\\2x=-14

Step 4: Divide both sides by 2.


(2x)/(2) =(-14)/(2)\\ x=-7

User Denis Troller
by
5.2k points
5 votes

Answer:


x = -7

Explanation:


6(3 - x) = -4(2x - 1) \\ \\\to 6 * 3 - 6 * x = -4 * 2x + 4 * 1 \\ \\\to 18 - 6x = -8x + 4 \text{ / Add 8x on both sides} \\ \\\to 18 + 2x = 4 \text{ / Subtract 18 on both sides} \\ \\\to 2x = -14 \text{ / Divide by 2} \\ \\\to x = -7

User Kassens
by
5.3k points